The Healing Elements of an Eclectic Life Skills Programme: Clients’ Perspectives - Alta Stone; Lana van Niekerk (Occupational Therapy International)
Conclusions: The dynamic interplay of healing factors, captured in the themes, facilitated healing. Self-reflection was integral to the creation of a bespoke, facilitated self-learning process with direct application in group members’ own lives.